Basel II and financial stability: An investigation of sensitivity and cyclicality of capital requirements based on QIS 2 - Balázs Zsámboki (Magyar Nemzeti Bank, 2007)
This study aims to analyse the sensitivity of capital requirements to changes in risk parameters (PD, LGD and M) by creating a model bank with a portfolio mirroring the average asset composition of internationally active large banks, as well as locally oriented smaller institutions participating in the QIS 5 exercise. Using historical data on corporate default rates, the dynamics of risk weights and capital requirements over a whole business cycle are also examined, with special emphasis on financial stability implications. The purpose of this paper is to contribute to a better understanding of the mechanism of Basel II and to explore the possible impacts of prudential regulation on cyclical swings in capital requirements.
Keywords: G21; G28; G32; 330; Basel II; credit risk; capital requirement; regulation; cyclicality; financial stability; Basler Akkord; Basler Akkord; Kreditrisiko; Kapitalbedarf; EU-Staaten